Power storage device
By employing a carbon negative electrode and a lithium composite oxide positive electrode with a cubic crystal structure, along with an ion-conducting medium, the battery addresses issues of cell expansion, maintaining energy and capacity density.
Patent Information
- Application Number
- JP2023168945
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-29
- Publication Date
- 2025-04-10
- Estimated Expiration
- 2043-09-29
AI Technical Summary
Existing lithium-ion batteries face issues with excessive cell expansion during charge and discharge, leading to particle cracking and conductive path disappearance, which decreases energy and capacity density.
The use of a carbon negative electrode and a positive electrode made of a specified lithium composite oxide with a cubic crystal structure, along with an ion-conducting medium between the electrodes, helps to suppress the volume change of the entire cell while maintaining energy and capacity density.
This configuration effectively reduces the volume change of the entire cell, eliminates the need for external restraints, and maintains the energy and capacity density of the battery.
Smart Images

Figure 2025059130000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electricity storage device. [Background technology]
[0002] Currently, the most common high-capacity lithium-ion batteries (LIBs) for vehicles use layered oxides (e.g., LiNi x Co y Mn 1-x-y O 2 ) and carbon materials such as graphite as the negative electrode active material are widely used. In LIBs with this configuration, the entire cell can expand excessively when repeatedly charged and discharged, which can lead to deterioration such as particle cracking and loss of conductive paths. Furthermore, measures such as externally restraining the cell must be taken to suppress the cell expansion, which can result in a decrease in capacity density and energy density. To address these issues, for example, LIBs using lithium titanate, which changes little in volume during charging and discharging, as the negative electrode active material (Non-Patent Document 1), and Li 1+x Ti y V z O 2 as the positive electrode active material (Patent Document 1), a binder that follows the volume change of the electrode structure accompanying charge and discharge (Patent Document 2), and a lithium buffer layer disposed between the negative electrode and the electrolyte and a porous layer disposed between the negative electrode and the current collector (Patent Document 3) have been proposed. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2023-68548 A [Patent Document 2] JP 2020-145193 A [Patent Document 3] JP 2022-136024 A [Non-patent literature]
[0004] [Non-Patent Document 1] Toshiba_SCiB_General Catalog_2301(https: / / www.global.toshiba / content / dam / toshiba / jp / products-solutions / battery / scib / pdf / SCiB_toshiba.pdf) Summary of the Invention [Problem to be solved by the invention]
[0005] However, in Non-Patent Document 1, the redox potential of lithium titanate is about 1.5 V versus lithium, which is higher than the carbon negative electrode, which is about 0.1 V, and therefore there is a problem that the energy density is reduced accordingly. In addition, in Patent Document 1, the volume change of the positive electrode can be suppressed, but the volume change is still large when viewed as a whole cell. In Patent Document 2, the binder can follow the volume change of the electrode structure accompanying charge and discharge, but the volume change of the whole cell cannot be suppressed. In Patent Document 3, there is a problem that the number of parts increases and the capacity density is reduced.
[0006] The present invention has been made to solve such problems, and has as its main object to suppress the change in volume of the entire cell while suppressing the decrease in energy density and capacity density. [Means for solving the problem]
[0007] In order to achieve the above object, the present inventors have conducted intensive research and have found that, when a carbon negative electrode and a positive electrode containing a specific lithium composite oxide as a positive electrode active material are used in an electricity storage device and the electrode density of the positive electrode is adjusted, it is possible to suppress a decrease in the energy density and capacity density of the cell while suppressing a change in the volume of the entire cell, and thus have completed the invention disclosed in this specification.
[0008] That is, the electricity storage device disclosed in this specification is a negative electrode having a carbon material as a negative electrode active material; General formula Li a Px M y O 2-z A z (However, M is one or more of Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, and Ge, A is one or more of F, Cl, Br, I, and S, and 0 < a < 2, 0 < x ≤ 0.09, 0 < y < 1, 0 ≤ z < 2 are satisfied.) A lithium composite oxide represented by the formula is used as a positive electrode active material, and the electrode density is 1 g / cm 3 or more and 2.4 g / cm 3 or less, and a positive electrode, an ion conduction medium that is interposed between the negative electrode and the positive electrode and conducts lithium ions, is provided.
[0009] Alternatively, the power storage device disclosed in this specification has a negative electrode using a carbon material as a negative electrode active material, a lithium composite oxide having a cubic crystal structure is used as a positive electrode active material, and the positive electrode active material has a unit cell volume V of the crystal structure during charging C PEAU and a unit cell volume V of the crystal structure during discharging D PEAU When, ΔV PEAU =(1 - V C PEAU / V D PEAU ) × 100, and the volume change rate ΔV PEAU is 6% or more and 10% or less, and the electrode density is 1 g / cm 3 or more and 2.4 g / cm 3 or less, and a positive electrode, an ion conduction medium that is interposed between the negative electrode and the positive electrode and conducts lithium ions, is provided.
Advantages of the Invention
[0010] In the present disclosure, the volume change of the entire cell can be suppressed while suppressing the decrease in capacity density and energy density. The reason for obtaining such an effect is presumed to be as follows. In the present disclosure, since a carbon material with a low redox potential is used as the negative electrode active material, the decrease in energy density can be suppressed more than when lithium titanate or the like is used. Although the carbon negative electrode has a large volume change during charging and discharging, when a positive electrode containing a predetermined lithium composite oxide and formed with a predetermined electrode density is used as the counter electrode, the volume change of the carbon negative electrode during charging and discharging is canceled by the volume change of the positive electrode, so that the volume change of the entire cell can be suppressed. As a result, it is possible to omit measures such as externally restraining the cell, and it is presumed that the decrease in capacity density and energy density can also be suppressed. [Brief description of the drawings]
[0011] [Figure 1] FIG. 2 is a schematic diagram showing an example of the configuration of an electricity storage device 20. [Diagram 2] FIG. 1 is an explanatory diagram of a cell used in a simulation. [Diagram 3] FIG. 2 is an explanatory diagram showing the results of operando XRD measurement. [Figure 4] 11 is a graph showing a simulation result. [Diagram 5] 11 is a graph showing a simulation result. [Figure 6] Graph showing experimental results. [Figure 7] 1A and 1B are explanatory diagrams showing the state of a lithium ion battery during discharging and charging. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The power storage device of the present disclosure includes a negative electrode having a carbon material as a negative electrode active material, a positive electrode having a specific lithium composite oxide as a positive electrode active material, and an ion conductive medium interposed between the negative electrode and the positive electrode and conducting lithium ions. This power storage device may be, for example, a lithium ion battery.
[0013] The negative electrode may be formed by, for example, mixing a negative electrode active material, a binder, and optionally a conductive material, adding an appropriate solvent to form a paste-like negative electrode material, applying it to the surface of a current collector, drying it, and compressing it to increase the electrode density as necessary. The negative electrode active material is a carbon material. The carbon material is preferably one that can absorb and release lithium, and examples of the carbon material include cokes, glassy carbons, graphites, non-graphitizable carbons, pyrolytic carbons, and carbon fibers. Among these, graphites (graphites) such as artificial graphite and natural graphite have an operating potential close to that of metallic lithium and can be charged and discharged at a high operating voltage, and are therefore preferred. The binder contained in the negative electrode plays a role of binding the active material particles and the conductive material particles, and can be, for example, fluorine-containing resins such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVdF), fluorine rubber, or thermoplastic resins such as polypropylene and polyethylene, ethylene propylene diene monomer (EPDM) rubber, sulfonated EPDM rubber, natural butyl rubber (NBR), etc., used alone or as a mixture of two or more kinds. In addition, a cellulose-based water-based binder or an aqueous dispersion of styrene butadiene rubber (SBR) can also be used. The conductive material contained in the negative electrode is not particularly limited as long as it is an electronic conductive material that does not adversely affect the battery performance of the negative electrode, and can be, for example, a mixture of one or two or more kinds of graphite such as natural graphite (scale graphite, scale graphite) and artificial graphite, acetylene black, carbon black, ketjen black, carbon whisker, needle coke, carbon fiber, and metals (copper, nickel, aluminum, silver, gold, etc.). Among these, carbon black and acetylene black are preferred as the conductive material from the viewpoint of electronic conductivity and coating property. As the solvent for dispersing the negative electrode active material, the binder, the conductive material, etc., for example, organic solvents such as N-methylpyrrolidone, dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethylenetriamine, N,N-dimethylaminopropylamine, ethylene oxide, and tetrahydrofuran can be used. In addition, a dispersant, a thickener, etc. can be added to water, and the active material can be made into a slurry with a latex such as SBR.As the thickener, for example, polysaccharides such as carboxymethylcellulose and methylcellulose can be used alone or as a mixture of two or more kinds. Examples of the coating method include roller coating such as an applicator roll, screen coating, doctor blade method, spin coating, bar coater, etc., and any of these can be used to obtain any thickness and shape. As the negative electrode current collector, in addition to copper, nickel, stainless steel, titanium, aluminum, baked carbon, conductive polymer, conductive glass, Al-Cd alloy, etc., for the purpose of improving adhesion, conductivity, and reduction resistance, for example, copper, etc., whose surface is treated with carbon, nickel, titanium, silver, etc. can also be used. The surface of these can also be oxidized. Examples of the shape of the current collector include foil, film, sheet, net, punched or expanded, lath, porous, foam, and fiber group formation. The thickness of the current collector is, for example, 1 to 500 μm. The electrode density of the negative electrode is 1 g / cm. 3 More than 2g / cm 3 It may be 1.3 g / cm or less. 3 More than 1.7g / cm 3 It may be 1.4 g / cm or less. 3 More than 1.6g / cm 3 The electrode density is the electrode density excluding the current collector. The active material ratio in the negative electrode (excluding the current collector) may be 90% by mass or more and 99.5% by mass or less, or 95% by mass or more and 99% by mass or less.
[0014] The positive electrode may be formed by mixing a positive electrode active material, a conductive material, and a binder, adding an appropriate solvent to form a paste-like positive electrode composite, applying it to the surface of a current collector, drying it, and compressing it to increase the electrode density as necessary. The positive electrode active material is a lithium composite oxide. The lithium composite oxide may contain, for example, one or more of Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, and Ge. The lithium composite oxide may also contain P. The lithium composite oxide may also contain one or more of F, Cl, Br, I, and S. The lithium composite oxide may be, for example, the lithium composite oxide disclosed in JP 2023-77491 A. Such lithium composite oxides are preferable because they have a high capacity density.
[0015] The positive electrode active material is of the general formula Li a P x M y O 2-z A zIt may be a lithium composite oxide represented by the following formula. However, M is one or more of Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, and Ge, A is one or more of F, Cl, Br, I, and S, and 0 < a < 2, 0 < x ≤ 0.09, 0 < y < 1, 0 ≤ z < 2 are satisfied. In this lithium composite oxide, the content x of P preferably satisfies 0.02 ≤ x ≤ 0.08, and more preferably satisfies 0.03 ≤ x ≤ 0.08. Further, the content y of the metal element M preferably satisfies 0.65 ≤ y < 1, and more preferably satisfies 0.7 ≤ y ≤ 0.95. Further, the content z of the element A preferably satisfies 0 ≤ z ≤ 1, and more preferably satisfies 0 ≤ z ≤ 0.5 or less. The content a of Li may satisfy 1 ≤ a ≤ 1.25 in the state where charge and discharge are not performed. This lithium composite oxide may contain at least one of the above-described transition metal elements (Ti, V, Cr, Mn, Fe, Co, Ni, Cu) as the metal element M, and preferably contains at least Mn. This lithium composite oxide may contain the element A (that is, the content z of the element A satisfies 0 < z). In the case of containing the element A (particularly F), when charge and discharge are repeated, there is an advantage that it is easy to estimate the state of charge (SOC) from the potential because the changes in the discharge curve and dQ / dV curve are small. When F is contained as the element A, the content z of F preferably satisfies 0 < z < 0.5, and may satisfy 0.3 ≤ z < 0.5. In this lithium composite oxide, it is preferable that the metal element M and P are uniformly distributed in the element distribution measured by STEM / EDX. Further, when this lithium composite oxide contains the element A, it is preferable that the metal element M, P, and element A are uniformly distributed in the element distribution measured by STEM / EDX. When the metal element M, P, and element A are uniformly distributed, it is preferable because the carrier ions (for example, lithium ions) of the power storage device are occluded and released into the lithium composite oxide without being biased.
[0016] The positive electrode active material may be a lithium composite oxide having a cubic crystal structure. Of these, the positive electrode active material is preferably a lithium composite oxide having a disordered rock salt structure (also called a random rock salt structure). The disordered rock salt structure shows a peak pattern in an XRD spectrum having four diffraction peaks in the range of 2θ from 35° to 39°, from 42° to 48°, from 62° to 68°, and from 80° to 84°. In addition, since it has a disordered structure, the diffraction peaks are relatively broad, with the half-width of the main peak at 2θ=42° to 48° being 1.5° or more, and the half-width of the peak at 2θ=62° to 68° being 2° or more.
[0017] The volume of the unit cell of the crystal structure during charging is V C PEAU , the volume of the unit cell of the crystal structure during discharge is V D PEAU When this is done, ΔV PEAU =(1-V C PEAU / V D PEAU ) × 100, which is the volume change rate ΔV PEAU It is preferable that the volume change rate ΔV is 6% or more and 10% or less. PEAU is preferably 7% or more, and more preferably 8% or more. PEAU may be set to 9% or less.
[0018] The conductive material, binder, solvent, etc. used in the positive electrode can be the same as those exemplified for the positive electrode. As the current collector, aluminum, titanium, stainless steel, nickel, iron, baked carbon, conductive polymer, conductive glass, etc., as well as aluminum or copper whose surface is treated with carbon, nickel, titanium, silver, etc. for the purpose of improving adhesion, conductivity, and oxidation resistance can be used. The surface of these can also be oxidized. The shape of the current collector can be a foil, film, sheet, net, punched or expanded, lath, porous, foam, or fiber group formation. The thickness of the current collector is, for example, 1 to 500 μm. The shape of the current collector can be the same as that of the negative electrode.
[0019] The electrode density of the positive electrode is 1 g / cm 3 More than 2.4g / cm 3 The electrode density of the positive electrode is preferably high from the viewpoint of increasing the capacity density and suppressing the volumetric shrinkage of the cell due to charging and discharging, and is, for example, 1.1 g / cm. 3 More than 1.2 g / cm is preferable. 3 From the viewpoint of suppressing the volume expansion of the cell due to charging and discharging, the electrode density of the positive electrode is preferably low, for example, 2.0 g / cm. 3 Less than 1.8 g / cm is preferred. 3 The following is more preferable. The electrode density is the electrode density excluding the current collector. The active material ratio in the positive electrode (excluding the current collector) may be 80% by mass or more and 97% by mass or less, or 85% by mass or more and 95% by mass or less. The capacity ratio of the negative electrode to the positive electrode may be more than 1.0 and 1.2 or less, or 1.05 or more and 1.15 or less.
[0020] The ion-conducting medium may be a non-aqueous electrolyte solution containing a supporting salt containing lithium and a non-aqueous solvent. Examples of the solvent for the non-aqueous electrolyte solution include carbonates, esters, ethers, nitriles, furans, sulfolanes, and dioxolanes, which may be used alone or in combination. Specific examples of carbonates include cyclic carbonates such as ethylene carbonate, propylene carbonate, vinylene carbonate, butylene carbonate, and chloroethylene carbonate; chain carbonates such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl-n-butyl carbonate, methyl-t-butyl carbonate, di-i-propyl carbonate, and t-butyl-i-propyl carbonate; cyclic esters such as γ-butyl lactone and γ-valerolactone; chain esters such as methyl formate, methyl acetate, ethyl acetate, and methyl butyrate; ethers such as dimethoxyethane, ethoxymethoxyethane, and diethoxyethane; nitriles such as acetonitrile and benzonitrile; furans such as tetrahydrofuran and methyltetrahydrofuran; sulfolanes such as sulfolane and tetramethylsulfolane; and dioxolanes such as 1,3-dioxolane and methyldioxolane. Of these, a combination of a cyclic carbonate and a chain carbonate is preferred.
[0021] The supporting salt is, for example, LiPF 6 , LiBF 4 , LiAsF 6 , LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 , LiC(CF 3 SO 2 ) 3 , LiSbF 6 , LiSiF 6 , LiAlF 4 , LiSCN, LiClO 4 , LiCl, LiF, LiBr, LiI, LiAlCl 4 Among these, LiPF 6 , LiBF 4, LiAsF 6 , LiClO 4 and inorganic salts such as LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 , LiC(CF 3 SO 2 ) 3 From the viewpoint of electrical properties, it is preferable to use one or more salts selected from the group consisting of organic salts such as those mentioned above in combination. The concentration of this supporting salt in the non-aqueous electrolyte is preferably 0.1 mol / L or more and 5 mol / L or less, and more preferably 0.5 mol / L or more and 2 mol / L or less. When the concentration of the supporting salt is 0.1 mol / L or more, a sufficient current density can be obtained, and when it is 5 mol / L or less, the electrolyte can be more stabilized.
[0022] The power storage device of the present disclosure may include a separator between the negative electrode and the positive electrode. The separator is not particularly limited as long as it has a composition that can withstand the range of use of the power storage device, and examples of the separator include polymer nonwoven fabrics such as polypropylene nonwoven fabrics and polyphenylene sulfide nonwoven fabrics, and thin microporous films of olefin resins such as polyethylene and polypropylene. These may be used alone or in combination.
[0023] In the electricity storage device of the present disclosure, the rate of change in the total volume of the negative electrode and positive electrode before and after charging and discharging is preferably within ±2%, more preferably within ±1.5%, and even more preferably within ±1%.
[0024] The power storage device of the present disclosure has a discharge capacity per cell volume of preferably 200 Ah / L or more, more preferably 220 Ah / L or more. The power storage device of the present disclosure may have a discharge capacity per cell volume of 300 Ah / L or less.
[0025] The power storage device of the present disclosure is not particularly limited, and examples include coin type, button type, sheet type, laminated type, cylindrical type, flat type, square type, etc. Further, it may be applied to large-sized devices in which a plurality of such power storage devices are connected in series and used for electric vehicles or the like. FIG. 1 is a schematic diagram showing an example of the power storage device 20 of the present embodiment. This power storage device 20 includes a sheet-like negative electrode 26 in which a negative electrode composite material 25 is formed on the surface of a current collector 24, a sheet-like positive electrode 23 in which a positive electrode composite material 22 is formed on a current collector 21, a separator 28 provided between the negative electrode 26 and the positive electrode 23, and a non-aqueous electrolyte 29 filling the space between the negative electrode 26 and the positive electrode 23. In this power storage device 20, the separator 28 is sandwiched between the negative electrode 26 and the positive electrode 23, and these are wound and inserted into a cylindrical case 32, and a negative electrode terminal 36 connected to the negative electrode 26 and a positive electrode terminal 34 connected to the positive electrode 23 are disposed. The negative electrode composite material 25 contains a carbon material such as graphite as a negative electrode active material. The positive electrode composite material 22 contains, for example, a lithium composite oxide represented by the general formula Li a P x M y O 2-z A z (However, M is one or more of Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, and Ge, A is one or more of F, Cl, Br, I, and S, and 0 < a < 2, 0 < x ≤ 0.09, 0 < y < 1, 0 ≤ z < 2 are satisfied.) as a positive electrode active material. The electrode density of the positive electrode (the density of the positive electrode composite material 22) is 1 g / cm 3 or more and 2.4 g / cm 3 or less.
[0026] In the power storage device of the present embodiment described in detail above, it is possible to suppress a decrease in the volume change of the entire cell while suppressing a decrease in the capacity density and the energy density. The reason for obtaining such an effect is presumed as follows. In the power storage device of the present embodiment, since a carbon material having a low redox potential is used as the negative electrode active material, a decrease in the energy density can be suppressed as compared with the case where lithium titanate or the like is used. Although the carbon negative electrode has a large volume change during charge and discharge, when a positive electrode containing a predetermined lithium composite oxide and formed at a predetermined density is used as the counter electrode, the volume change of the carbon negative electrode is canceled out by the volume change of the positive electrode during charge and discharge. Therefore, the volume change of the entire cell can be suppressed. As a result, it is presumed that a treatment such as restraining the cell from the outside can be omitted, and a decrease in the capacity density and the energy density can also be suppressed.
[0027] Note that the present disclosure is not limited to the above-described embodiments at all, and it goes without saying that the present disclosure can be implemented in various modes as long as it belongs to the technical scope of the present disclosure.
[0028] For example, the present disclosure may be any of the following [1] to [7]. [1] A negative electrode using a carbon material as a negative electrode active material, a general formula Li a P x M y O 2-z A z (However, M is one or more of Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, and Ge, A is one or more of F, Cl, Br, I, and S, and 0 < a < 2, 0 < x ≦ 0.09, 0 < y < 1, 0 ≦ z < 2 are satisfied.) A power storage device comprising a lithium composite oxide represented as a positive electrode active material, a positive electrode having an electrode density of 1 g / cm 3 or more and 2.4 g / cm 3 or less, and an ion conduction medium interposed between the negative electrode and the positive electrode and conducting lithium ions. [2] The positive electrode active material has a cubic crystal structure, and the volume of the unit cell of the crystal structure during charging is V C PEAU , and the volume of the unit cell of the crystal structure during discharging is V D PEAUWhen this is done, ΔV PEAU =(1-V C PEAU / V D PEAU ) × 100, which is the volume change rate ΔV PEAU The power storage device according to [1], wherein the ratio of the capacitance to the capacitance of the power storage device is 6% or more and 10% or less. [3] A negative electrode using a carbon material as the negative electrode active material and a lithium composite oxide having a cubic crystal structure as the positive electrode active material, the volume of the unit cell of the crystal structure during charging is V C PEAU , the volume of the unit cell of the crystal structure during discharge is V D PEAU When this is done, ΔV PEAU =(1-V C PEAU / V D PEAU ) × 100, which is the volume change rate ΔV PEAU is 6% or more and 10% or less, and the electrode density is 1g / cm 3 More than 2.4g / cm 3 and an ion conductive medium interposed between the negative electrode and the positive electrode and conducting lithium ions. [4] The electricity storage device according to any one of [1] to [3], wherein the negative electrode active material is graphite. [5] The density of the positive electrode is 1.2 g / cm 3 More than 1.8g / cm 3 The electricity storage device according to any one of [1] to [4] below. [6] The electricity storage device according to any one of [1] to [5], wherein a rate of change in the total volume of the negative electrode and the positive electrode before and after charging and discharging is within ±2%. [7] The electricity storage device according to any one of [1] to [6], wherein the discharge capacity per cell volume is 200 Ah / L or more. EXAMPLES
[0029] Hereinafter, a specific example of a lithium ion battery, which is an example of the power storage device of the present disclosure, will be described as an example. In addition, among Experimental Example 1, Experimental Examples 1-1 to 1-8 and Experimental Example 1-15 correspond to Examples, and Experimental Examples 1-9 to 1-14 correspond to Comparative Examples. Moreover, Experimental Examples 2 to 4 all correspond to Comparative Examples.
[0030] [Experimental Example 1 (Experimental Examples 1-1 to 1-14)] 1. Simulation of cell volume change rate As shown in Figure 2, a cell consisting of a positive electrode and a negative electrode facing each other vertically was examined. The volume of the positive electrode active material is V PEA [cm 3 ] and the volume of the negative electrode active material is V NEA [cm 3 The volume of the positive electrode mixture is V PE [cm 3 ] and the volume of the negative electrode mixture is V NE [cm 3 ]. Also, a certain unit area S [cm 2 Consider the cell cut out at ], and the thickness of the positive electrode is l PE [μm] and the negative electrode thickness is l NE The cell volume V of the part whose volume changes during charging and discharging is all [cm 3 ] is defined by the following formula (1), and V before and after charging and discharging all The rate of change of ΔV all I researched the following.
[0031]
number
[0032] The positive and negative active materials are + The volume of the crystal lattice changes before and after the insertion and removal of the charge. The volume of the unit cell of the crystal structure of the positive electrode active material is V PEAU [Å 3 ] and the volume of the unit cell of the crystal structure of the negative electrode active material is V NEAU [Å 3 ] and V PEAU and V NEAUwas calculated from the peak position of X-ray diffraction (XRD). V PEAU V C PEAU , V during discharge PEAU V D PEAU Then, V before and after charging and discharging PEAU The rate of change of ΔV PEAU is expressed by the following formula (2).
[0033]
number
[0034] The positive electrode active material used in the simulation was Li 0.90 Mn 0.84 P 0.04 O 2 (LMPO). From the pre-operando XRD experiment described later, ΔV PEAU The capacity per LMPO, Q, was calculated to be 8.73%. PEA The capacity was 346mAh / g. 0.90 Mn 0.84 P 0.04 O 2 (LMPO) was determined to have a cubic crystal structure (specifically, a disordered rock salt structure) by XRD.
[0035] The negative electrode active material used in the simulation was standard natural graphite. The true density of natural graphite is 2.2 g / cm3 during charging and discharging. 3 from 2g / cm 3 That is, the V before and after charging and discharging NEAU The rate of change of ΔV NEAU The capacity of natural graphite, Q NEAis 350 mAh / g based on S. Schweidler, L. de Biasi, A. Schiele, P. Hartmann, T. Brezesinski, J. Janek, The Journal of Physical Chemistry C 2018, 122, 8829-8835.
[0036] In the cell used in the simulation, the active material ratio of the positive electrode w PEA The electrode density of the positive electrode, c PEA is 1.0g / cm 3 ~3.6g / cm 3 The ratio of the active material in the negative electrode w NEA is 98 mass %, and the mass of the active material of the negative electrode ρ NEA is 7.5 mg / cm 2 , the electrode density of the negative electrode c NEA is 1.5g / cm 3 The capacity ratio of the negative electrode to the positive electrode was 1.1. The active material weight of the positive electrode was ρ PEA And placed it there.
[0037] Based on the above assumptions, the amount of active material per unit area of the positive electrode ρ is calculated from the following formula (3). PEA [mg / cm 2 ] and calculate the positive electrode thickness l from the following formula (4). PE [μm] was calculated, and the positive electrode volume V was calculated based on the result, which is expressed by the following formula (5). PE asked for.
[0038]
number
[0039] In addition, the negative electrode thickness l is calculated from the following formula (6): NE [μm] is calculated, and the negative electrode volume V NE asked for.
[0040]
number
[0041] By applying the above results to the above formula (1), the cell volume V of the part whose volume changes during charging and discharging is calculated. all was calculated.
[0042] Furthermore, when the volume of the active material changes during charging, it is most likely that the positive and negative electrodes will change in the same manner as the volume of the active material changes during charging. Based on the above calculations, the change in cell volume before and after charging and discharging, ΔV all Calculated. ΔV all is ΔV all =(V all (Before charging) -V all (After charging))×100 / V all The capacity per cell volume, Q [Ah / L], was calculated using the following formula (8):
[0043]
number
[0044] 2. Preparation of Positive Electrode Li as the positive electrode active material 0.90 Mn 0.84 P 0.04 O 2 (LMPO) was synthesized. The raw material was orthorhombic LiMnO 2 was placed in a zirconia pot together with zirconia balls and ground in a planetary ball mill at 560 rpm for 28 h to obtain LiMnO with a disordered rock salt phase. 2 The powder was obtained. The raw material was LiMnO 2 and Li 3 PO 4 Li 3 PO 4 The mixture was mixed in an agate bowl so that the weight fraction of was 5%, then sealed in a zirconia pot together with zirconia balls and ground in a planetary ball mill at 600 rpm for 36 hours to obtain Li with a cubic crystal phase. 0.90 P 0.04 Mn 0.84 O 2A positive electrode active material was synthesized. 85% by mass of the synthesized LMPO positive electrode active material, 10% by mass of carbon black (CB, TB5500, manufactured by Tokai Carbon), and 5% by mass of a binder (polyvinylpyrrolidone, manufactured by Kishida) were mixed, and the mixture was applied onto an Al foil and dried to prepare a positive electrode.
[0045] 3. Operando XRD of Positive Electrode Operando XRD was performed to investigate the change in the crystal lattice constant during charge and discharge for the positive electrode prepared as described above. A half cell was prepared by combining the LMPO positive electrode and a metallic Li counter electrode with a separator (E20MMS) and electrolyte, and XRD patterns were obtained at BL33XU of SPring-8 while performing constant current and constant voltage charge and discharge measurements. The electrolyte was a mixed solvent containing 30 vol% ethylene carbonate (EC), 40 vol% dimethyl carbonate (DMC), and 30 vol% ethyl methyl carbonate (EMC), with LiPF 6 The constant current and low voltage charge / discharge measurements were performed at 4.8 to 1.5 V vs. Li + The current was adjusted to 20 mA / g per mass of the positive electrode active material in the potential range of 1000 V / Li.
[0046] Figure 3 shows the results of the operando XRD measurement. Figure 3 also shows the change in the lattice constant calculated from the operando XRD pattern. From this, it was found that the LMPO current was 4.075 A during charging and 4.17 A during discharging, and the ΔV PEAU was calculated to be 8.73%.
[0047] 4. Preparation of the Negative Electrode A negative electrode was prepared by mixing 98% by mass of graphite, 1% by mass of carboxymethyl cellulose, and 1% by mass of PVdF, applying the mixture to a Cu foil and drying it. NEA is 7.5 mg / cm 2 and the negative electrode density c NEA is 1.5g / cm 3 It was decided.
[0048] 5.Measuring the thickness of lithium-ion batteries A full-cell lithium-ion battery was fabricated using the LMPO positive electrode and graphite negative electrode prepared as described above. The full cell was fabricated by placing the positive and negative electrodes facing each other in an Al laminate of 60 × 100 mm with a polyethylene separator between them. The electrolyte was the same as that of the half-cell described above. The final voltage during charge and discharge was 4.7 to 1.4 V, and the current value was 20 mA / g per mass of the positive electrode active material. The thickness of the cell was measured at four points using a thickness gauge during the first charge and discharge. The cell volume was calculated by subtracting the thickness of the current collector, Al laminate, and separator from the thickness obtained. The results were calculated using the average of the four measured points.
[0049] [Experimental Example 2] The positive electrode active material is LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 The same procedure was followed as in Experimental Example 1, except that NCM111 was used. Based on the data in AO Kondrakov, et. al., The Journal of Physical Chemistry C 2017, 121, 3286-3294., the ΔV PEAU is 1.16%, and Q PEA was set at 149mAh / g.
[0050] [Experimental Example 3] The positive electrode active material is LiNi 0.8 Co 0.1 Mn 0.1 O 2 The same procedure was followed as in Experimental Example 1, except that NCM811 was used. Based on the data in AO Kondrakov, et. al., The Journal of Physical Chemistry C 2017, 121, 3286-3294., the ΔV PEAU is 1.45%, and Q PEA was set at 189mAh / g.
[0051] [Experimental Example 4] The positive electrode active material is LiMn 2 O 4The same procedure was followed as in Experimental Example 1, except that: 2 O 4 ΔV PEAU is 7.45%, and Q PEA was set to 110mAh / g.
[0052] [Results and Discussion] Figure 4 shows the positive electrode density c PE When changing V before and after charging and discharging all The results of a simulation of the change rate (%) of the positive electrode active material and the capacity per cell volume (Ah / L) are shown in Fig. 4A. 0.90 Mn 0.84 P 0.04 O 2 When LiNiPO was used (Experimental Example 1), Fig. 4B shows 1 / 3 Co 1 / 3 Mn 1 / 3 O 2 When (NCM111) was used (Experimental Example 2), Fig. 4C shows LiNi 0.8 Co 0.1 Mn 0.1 O 2 When LiMn (NCM811) was used (Experimental Example 3), Fig. 4D shows 2 O 4 This is the result when the above was used (Experimental Example 4).
[0053] These results indicate that NCM111, NCM811, and LiMn 2 O 4 It was found that when LMPO was used as the positive electrode active material and graphite was used as the negative electrode, there was no condition under which the cell volume change rate before and after charging and discharging was within ±1%. On the other hand, when LMPO was used as the positive electrode active material, the positive electrode density was 1.4 to 1.6 g / cm 3 Nearby is V all It was found that the rate of change was within ±1%.
[0054] 4A to 4D, V before and after charging and discharging all The rate of change of ΔV allThe relationship between the discharge capacity per cell volume and the capacity at each positive electrode active material is shown in Figure 5. Table 1 summarizes the simulation results under conditions 1 to 7 shown in the figure.
[0055] [Table 1]
[0056] Condition 1 (LMPO positive electrode with density of 1.4 g / cm 3 In the V all The change in volume was -0.1%, which meant that there was almost no change in volume. The capacity Q per cell volume was 226 Ah / L. Condition 2 (LMPO positive electrode with density 3.0 g / cm 3 In the case of the 100%-capacity lithium-ion battery, the capacity per cell volume Q is expected to be the highest at 312 Ah / L, but V all The rate of change of ΔV all The battery life is 3.1%, so deterioration is expected over the long term, and external restraints are required. Conditions 3, 4, 5, and 6 are combinations of positive and negative electrodes that are currently commonly used in automotive lithium-ion batteries. all The rate of change of ΔV all It was found that external constraint was required because the value of LiMn 2 O 4 The positive electrode has a density of 3.0 g / cm 3 In the case of V all The rate of change of ΔV all The change in volume was large, at -1.5%, outside the ±1% range. The capacity per cell volume was also 190 Ah / L, lower than when NCM or LMPO were used for the positive electrode. Table 2 shows the change in cell volume and capacity per volume relative to the positive electrode density when the LMPO positive electrode was used. It was found that a positive electrode density of 1.2 to 1.8% is preferable to keep the cell volume change rate to -1 to 1%.
[0057] [Table 2]
[0058] A full cell was actually produced using an LMPO positive electrode, an NCM811 positive electrode, and a graphite negative electrode, and the change in cell volume during charging and discharging was estimated by the thickness measurement described above. The results are shown in FIG. 6 and Table 3. The cell using the LMPO positive electrode expanded by 1.7% during charging, but there was almost no change in the cell volume during discharging. On the other hand, when the NCM811 positive electrode was used, the cell expanded by 16% during charging and contracted by 16% during discharging. This was a value larger than the cell expansion and contraction rate expected from the simulation, but it was thought that this was largely due to measurement errors, and the cell expansion and contraction generally coincided with the simulation. From the above, it was found that in a conventional high-capacity lithium-ion battery, as shown in FIG. 7A, the expansion and contraction of the carbon negative electrode could not be absorbed during charging and discharging, and the expansion and contraction of the entire cell was large, whereas in the lithium-ion battery of the present disclosure, as shown in FIG. 7B, the expansion and contraction of the carbon negative electrode can be absorbed by the expansion and contraction of the positive electrode during charging and discharging, so that the expansion and contraction of the entire cell is suppressed.
[0059] [Table 3] [Industrial Applicability]
[0060] The present disclosure is applicable to technical fields of the battery industry, etc. [Explanation of symbols]
[0061] 20 electricity storage device, 21 current collector, 22 positive electrode mixture, 23 positive electrode, 24 current collector, 25 negative electrode mixture, 26 negative electrode, 28 separator, 29 non-aqueous electrolyte, 32 cylindrical case, 34 positive electrode terminal, 36 negative electrode terminal.
Claims
1. a negative electrode having a carbon material as a negative electrode active material; General formula Li a P x M y O 2-z A z (wherein M is one or more of Al, Si, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, and Ge, and A is one or more of F, Cl, Br, I, and S, and satisfies 0<a<2, 0<x≦0.09, 0<y<1, 0≦z<2), and the positive electrode active material is a lithium composite oxide represented by the following formula (1): 3 2.4g / cm or more 3 A positive electrode, an ion conductive medium interposed between the negative electrode and the positive electrode and conducting lithium ions; The power storage device includes:
2. The positive electrode active material has a cubic crystal structure, and the volume of a unit cell of the crystal structure during charging is V C PEAU , the volume of the unit cell of the crystal structure during discharge is V D PEAU When this is done, ΔV PEAU = (1-V C PEAU / V D PEAU ) × 100 PEAU is 6% or more and 10% or less, The power storage device according to claim 1 .
3. a negative electrode having a carbon material as a negative electrode active material; A lithium composite oxide having a cubic crystal structure is used as a positive electrode active material, and the volume of a unit cell of the crystal structure during charging is V C PEAU , the volume of the unit cell of the crystal structure during discharge is V D PEAU When this is done, ΔV PEAU = (1-V C PEAU / V D PEAU ) × 100 PEAU is 6% or more and 10% or less, and the electrode density is 1 g / cm 3 2.4g / cm or more 3 A positive electrode, an ion conductive medium interposed between the negative electrode and the positive electrode and conducting lithium ions; The power storage device includes:
4. The negative electrode active material is graphite. The electricity storage device according to any one of claims 1 to 3.
5. The electrode density of the positive electrode is 1.2 g / cm 3 1.8g / cm or more 3 Below is the The electricity storage device according to any one of claims 1 to 3.
6. The rate of change in the total volume of the negative electrode and the positive electrode before and after charging and discharging is within ±2%. The electricity storage device according to any one of claims 1 to 3.
7. The discharge capacity per cell volume is 200 Ah / L or more. The electricity storage device according to any one of claims 1 to 3.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2010015904A
Secondary battery
JP2010232011A
Lithium secondary battery
JP2011071017A
Carbon nanotube dispersion, composition for secondary battery electrodes using the same, electrode membrane, secondary battery
JP2021176140A
Carbon fiber aggregate and method for manufacturing same, and electrode mixture layer for nonaqueous-electrolyte secondary cell
WO2020045243A1